The effect of light intensities on morpho-physiological and biochemical of black pepper (Piper nigrum L.) - Issukindarsyah; Sulistyaningsih Endang; Indradewa Didik; Putra Eka T. Susila (E3S Web of Conferences, 2021)
The difference in the levels of light intensity was responded with changes in morphophysiological and biochemical characters of plants, especially in leaves of black pepper. The aim of this study was to determine the effect of several levels of light intensity on the morphophysiological and biochemical characters of leaves of black pepper. The research was conducted in July - November 2017 in Kemuja, Mendobarat, Bangka Belitung. This study used split-plot design with three replications. The main plots were the levels of light intensity, namely 100%, 75%, and 50%. Subplots were varieties of black pepper, namely Petaling 1, Petaling 2, and Nyelungkup. The results showed that there was no interaction between varieties and light intensities. The morphophysiological and biochemical responses of the leaves of the three varieties tested were the same at all levels of light intensity. Light intensity up to 50% has no effect on leaf morphological characters, but leaves become thinner at lower light intensities. Chlorophyll, nitrate reductase activity and leaf sucrose concentration were same at all light intensities up to 50%. Plants exposed to higher light intensity have a higher number of stomata. The results concluded that the light intensity of up to 50% did not cause changes in leaf morphology and biochemistry and only affected leaf stomata density.